An in-depth human health risk assessment of potentially toxic elements in highly polluted riverine soils, Příbram (Czech Republic) - Kebonye, Ndiye M; Eze, Peter N; John, Kingsley; Agyeman, Prince C; Němeček, Karel; Borůvka, Luboš (Environmental geochemistry and health, 2022)
Environmental pollution by potentially toxic element (PTE) and the associated health risks in humans are increasingly becoming a global challenge. The current study is an in-depth assessment of PTEs including the often studied lead (Pb), manganese (Mn), zinc (Zn), arsenic (As) and the less-studied titanium (Ti), rubidium (Rb), strontium (Sr), zirconium (Zr), barium (Ba) and thorium (Th) in highly polluted floodplain topsoil samples from the Litavka River, Czech Republic. Soil chemical properties including carbon (Cox) and reaction (pH_H2O) together with iron (Fe) were assessed in the same soils. A portable X-ray fluorescence spectrometer (p-XRFS) (Delta Premium) was used to measure the PTEs and Fe contents of the soils. Soil organic carbon and reaction pH were determined following routine laboratory procedures. The concentration level of each PTE was compared against world average and crustal values, with the majority of elements exceeding the aforementioned geochemical background levels. Distributions of the PTEs were mapped. Two pollution assessment indices including enrichment factor (EF) and pollution index (PI) levels were calculated and their means for Zn (43.36, 55.54), As (33.23, 43.59) and Pb (81.08, 103.21) show that these elements were enriched. Zn, As and Pb accounted for the high pollution load index (PLI) levels observed in the study. The EF and PI distribution maps corresponded with the concentration distribution maps for each PTE. On health risk assessment, hazard quotients (HQ) in different human groups varied. Children had the highest HQs for all PTEs than adults (women and men). PTEs with high HQ levels in distinct human groups were As, Zr and Pb. Zirconium is a less likely element to pose a health risk in humans. Nonetheless, it should be kept in check despite its low pollution occurrence.
Keywords: dospělí; hodnocení rizik; Female; dítě; Adult; Litavka River; Soil Pollutants; ženské pohlaví; monitorování životního prostředí; Secondary pollution; látky znečišťující půdu; lidé; Potentially toxic elements; Risk Assessment; těžké kovy; Czech Republic; Environmental Monitoring; Česká republika; Child; Soil; půda; Riverine soils; Carbon; uhlík; Metals, Heavy; Health-risk assessment; Humans